KWL Plus Strategy Improves Ninth Grade Reading Comprehension Achievement - Indah Nur Fita; Dian Novita (Academia Open, 2025)
General Background: Reading is a complex cognitive process requiring integration of linguistic skills, prior knowledge, and comprehension strategies. Specific Background: Many junior secondary students struggle to understand English texts, particularly recount texts, due to low interest, limited practice, and difficulty grasping content meaning. Knowledge Gap: Although various instructional strategies exist, the KWL Plus strategy has not been implemented at the studied school, leaving uncertainty about its classroom outcomes in this context. Aims: This study investigates whether the KWL Plus strategy improves ninth-grade students’ reading comprehension achievement compared with conventional instruction. Results: Using a true experimental pretest–posttest design with experimental and control groups, both groups showed significant score gains, but the experimental group achieved a higher mean increase (14.040) than the control group (7.083), with significance values of 0.000. Novelty: The study provides empirical evidence from a setting where the strategy had not previously been applied, demonstrating stronger gains under structured metacognitive instruction. Implications: The findings suggest that incorporating KWL Plus into English reading lessons can support more active learning, deeper text understanding, and improved academic performance in junior secondary classrooms. Highlights: Students receiving the intervention achieved substantially larger score gains than peers in conventional classes. Statistical testing confirmed meaningful differences between initial and final assessments in both groups. Structured metacognitive activities promoted stronger engagement with recount texts. Keywords: KWL Plus strategy; Reading Comprehension; Ninth Grade Students; True Experimental Design; English Language Learning